Assessing the Utilization of Indigenous Feed Alternatives by Backyard Poultry Farmers: A Survey in Zamboanga del Sur, Philippines - Enario, Gether (International Journal of Scientific Research and Management (IJSRM), 2025)
Backyard poultry farming is a vital livelihood activity among rural households in the Philippines. However, the rising cost of commercial feeds has prompted interest in using alternative and indigenous feed resources. This study aimed to assess the Wextent of utilization, knowledge, and challenges of backyard poultry farmers regarding indigenous feed alternatives in Zamboanga del Sur. Using a descriptive research design, data were gathered from 185 purposively selected respondents through a validated and reliable structured questionnaire. Results showed that most farmers were adults with limited formal education, predominantly female, and engaged in small-scale poultry production, mainly raising native chickens. A majority practiced mixed feeding strategies, combining commercial and alternative feeds, with corn, copra meal, and rice bran being the most utilized alternatives. Although high-potential feed ingredients like Azolla and Trichanthera gigantica were less used, factors such as limited awareness and technical knowledge were identified as barriers to broader adoption. Correlation and regression analyses revealed that knowledge significantly influenced the level of adoption, while challenges posed constraints. Thus, there is a need for targeted education, training programs, and extension services to promote further adoption of alternative feeds.